HUBUNGAN UNDERLYING FACTORS DENGAN KEJADIAN STUNTING PADA ANAK 1-2 TH - Candra, Aryu (Universitas Diponegoro, 2013)
ABSTRACTIntroductionStunting is short stature due to chronic malnutrition. Prevalence of stunting in childrenunder five years in Indonesia is high, more than 35%. Risk factors of stunting arecategorized as basic factors, underlying factors, and immediate factors. Researcher wantsto know what factors in underlying factors that influence stunting at children 1-2 yearsold.MethodsThis was a case control study, completed with qualitative study about the occurrence ofstunting at low and middle economic status. Samples were 58 cases and 58 controls.Datawere analyzed by univariate analysis, bivariate analysis with chi square test, andmultivariate analysis with multiple logistic regression.ResultThe multivariate analysis result show that risk factors of stunting at children 1-2 years oldare, low economic status (money spent for food consumption <Rp 25.000,-) (p=0,047;OR=2,43; CI=1,01-5,15), birth distance <2 years (p=0,024; OR=11,65; CI=1,38-98,3),and number of children in family >2 (p=0,002; OR=4,08; CI=1,65-10,85) (p=0,002;OR=4,08; CI=1,65-10,85). Risk factors which are not proven to influence the incidenceof stunting are age of mother when getting pregnant, mother?s levels of education,father?s level of education, and father?s smoking history.ConclusionRisk factors that influence the incidence of stunting in children 1-2 years old are loweconomic status, birth distance <2 years, and number of children in family >2. Keywords: stunting, malnutrition, children, growth, risk factors